The Effect of Clinical Simulation on the Cognitive Learning Abilities of Undergraduates of Silliman University College of Nursing - Galvez, Barbara Lyn A.; Caluscusan, Kathleah S.; Teh, Renee Felisa O. (Silliman Journal, 2022)
This paper will describe the effect of clinical simulation using high-fidelity patient simulator on the cognitive learning abilities of undergraduates of Silliman University College of Nursing based on their performance in written tests. The test scores in the pretest were compared with the result in the test scores after the conduct of simulation in the experimental group. The results derived from the experimental group were compared with the test results of the control group that did not undergo simulation. The test scores indicated that clinical simulation was irrelevant as an additional learning strategy to enhance their knowledge base. The clinical simulation with the use of high-fidelity patient simulator did not enhance the cognitive knowledge these students (N = 31) already possessed especially when their knowledge base was already concreted by other methods. Mastery level of the concept and subject matter harnessed by other methods was more effective than applying the same to a near or close to real scenario using a high-fidelity simulator.